Use of Different O/W or W/O Emulsions as Functional Ingredients to Reduce Fat Content and Improve Lipid Profile in Spanish Cured Processed Meat Product (‘Chorizo’) - Martínez, Elena; Vieira Júnior, Wagner Goncalves [UNESP]; Álvarez-Ortí, Manuel; Rabadán, Adrián; Pardo, José Emilio (MDPI, 2024)
In this work, three out of five types of oil-in-water and water-in-oil emulsions were selected to replace pork backfat to reduce the fat content and the improve monounsaturated and polyunsaturated fatty acid content in dry cured sausage (‘chorizo’). Different characteristics of the new product were studied: the texture profile, color, nutritional value, lipid profile, vitamin E and thiobarbituric acid (TBA) and sensory qualities. The use of emulsions to replace the animal fat affected all color parameters, obtaining darker, less red and yellow products, which could impact the consumer’s purchase intention. This replacement also altered the texture parameters, increasing or decreasing the hardness in comparison with the control sample. The cohesiveness, however, decreased in all cases, which meant that when the samples are cut for consumption, they disintegrated more than the traditional ones. The most relevant aspect for nutritional value is that the use of the new emulsions helped to reduce the total fat and energy value of the reformulated samples. The most significant aspect is that this reformulation helped to reduce the fat content—specifically, saturated fat—while increasing the content of Omega 3/6. The new formulas contained significant quantities of TBA and vitamin E when comparing them with the traditional product.
Keywords: consumer preference; dry cured sausages; functional food; oil emulsion; recovery waste; reformulated meat products